Beginning reading in Bicol - Magistrado, Gloria Vergara 1931- (1968)
This paper presented a new approach and a set of reading materials for beginning reading in Bicol with the aim in view of making the beginning reading activity a pleasure. The method used in the study was the phono-syllabic method. It was concluded that in order to make the lessons interesting, the sounds should be taught through interesting games and rhymes in playful teaching situations until unconsciously the children are able to remember the sounds by heart and at the same time enjoying the learning process.
"June, 1968."
Vita.
Thesis (M.A.T. : Reading)--University of the Philippines, Diliman
Keywords: Reading (Primary) -- Philippines -- Bicol